MENGEMBANGKAN TOLERANSI MASYARAKAT MELALUI PILOT PROJECT DESA PANCASILA - Warsito; Nur’aini, Dhiva Maulida Rizqi; Aji, Wisnu Nugroho; Wijayanti, Septiana; Widayanti, Sukasih Ratna; Santoso, Gunawan Budi (LPPM Universitas Widya Dharma Klaten, 2025)
Globalization has not only had a positive impact on tolerance, but also a negative one. The pilot project for the launch of the Pancasila Village is one effort to develop community tolerance. This study has three objectives: (1) to determine the implementation model for the Pancasila Village pilot project in developing community tolerance, (2) to identify the reasons why the launch of the Pancasila Village is appropriate at this time, and (3) to determine the extent of community participation in ensuring the success of Pancasila Village programs. This community service activity was carried out through methods of outreach, training, technology application, mentoring and evaluation, and program sustainability. The study concluded that, first, the implementation model for the Pancasila Village pilot project in developing community tolerance involved both physical and non-physical activities. Physical activities included installing street signs, displaying the national emblem on each house, and naming the Ngemplak Village field as the Pancasila Village Field. Non-physical activities included focus group discussions (FGDs), outreach, outreach, and so on. Second, the rationale for declaring Ngemplak Village a Pancasila Village is appropriate at this time because of the deviant behaviors and inferiority complexes resulting from globalization. Third, community participation in the success of the Pancasila Village, in efforts to develop societal tolerance, is significant and urgent.